Analysis of combined low-level indicators for the hot-season performance of roof components. (November 2022) - Lodi, Chiara; Muscio, Alberto; Tartarini, Paolo; Akbari, Hashem
Abstract: A single performance indicator, the solar transmittance factor (STF), has been proposed in previous works, together with the derived solar transmittance index (STI). It is aimed at evaluating the summer performance of the roofing system and allowing the selection of the most effective mix of surface and mass properties. It is easily calculated from low-level indicators such as U-value, module of periodic thermal transmittance, and solar reflectance. In the present work, the correlation between STF and the cooling energy demand, integrated over a reference period, was studied, as well as the peak of ceiling temperature increase with respect to the indoor temperature, relevant for thermal comfort. In particular, the thermal behavior of different roof types with variable insulation was calculated numerically by TRNSYS 17 for a wide set of locations and environmental conditions. Unlike other commonly used indicators, to which the analysis has been extended, a strong correlation with STF was found for both cooling energy demand and ceiling temperature rise.